2011
DOI: 10.1038/hr.2011.155
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease in postmenopausal women

Abstract: Menopause is derived from the Greek words men (month) and pauses (cessation) and means permanent cessation of menstruation after the loss of ovarian activity. Chronic kidney disease (CKD) has recently been associated with cardiovascular events in several studies. CKD patients have a heavy burden of traditional cardiovascular risk factors in addition to a range of nontraditional risk factors such as inflammation and abnormal metabolism of calcium and phosphate. In this review, the association of CKD and cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 89 publications
0
24
0
2
Order By: Relevance
“…Unlike in younger women, the earlier osmotic AVP threshold is associated with greater water and sodium retention (Stachenfeld et al 1998). Sodium also plays an important role in hypertension and progression of chronic kidney disease in postmenopausal women (Pechere-Bertschi & Burnier, 2004), and salt sensitivity correlates inversely with levels of circulating oestrogens and progesterone (Suzuki & Kondo, 2012). A recent study demonstrated greater desmopressin-induced water retention in older women, which could increase their risk of hyponatraemia (Juul et al 2011).…”
Section: Figure 3 Mean Plasma Arginine Vasopressin Concentration (P mentioning
confidence: 99%
“…Unlike in younger women, the earlier osmotic AVP threshold is associated with greater water and sodium retention (Stachenfeld et al 1998). Sodium also plays an important role in hypertension and progression of chronic kidney disease in postmenopausal women (Pechere-Bertschi & Burnier, 2004), and salt sensitivity correlates inversely with levels of circulating oestrogens and progesterone (Suzuki & Kondo, 2012). A recent study demonstrated greater desmopressin-induced water retention in older women, which could increase their risk of hyponatraemia (Juul et al 2011).…”
Section: Figure 3 Mean Plasma Arginine Vasopressin Concentration (P mentioning
confidence: 99%
“…Likewise, the percentage of women with diabetes was high, which could favour their appearance . Other factors like urinary retention and a high post‐void residual urine that have been also associated with urinary infections were not analyzed in the present study. However, they are common in older women …”
Section: Discussionmentioning
confidence: 83%
“…Post‐menopause is linked to an impaired function of the genitourinary tract. Thus, vulvovaginal atrophy, sexual dysfunctions, urine retention, urinary incontinence (UI), renal dysfunctions, and urinary infections are common among post‐menopausal women . Moreover, genitourinary dysfunctions worsen the quality of life of women …”
Section: Introductionmentioning
confidence: 99%
“…The subjects 50 years and older were enrolled in our study because kidney diseases in older people, especially menopausal women, have generally been shown to be related with the sex hormones through the renin-angiotensin-aldosterone system 12). A total of 3,011 subjects received their routine health examination between May 2008 and April 2010 at Konkuk University medical center.…”
Section: Methodsmentioning
confidence: 99%